Pendidikan Kesehatan Demam Berdarah Dengue Meningkatkan Upaya Pencegahan Kejadian Luar Biasa - Ketut Sudiantara; I Wayan Mustika; Putu Santika Dewi (Jurnal Gema Keperawatan, 2017)
The purpose of this study is to find out the health education of dengue fever increases the prevention of extraordinary events. This research is a quantitative study with Pre Experimental approach with Static Group Comparison. The population is 335 KK with the number of research sample 46 KK Banjar Ubud Kelod area UPT Kesmas Ubud I selected with sampling technique Simple Random Sampling. Data collection tools which is used is kuisioner. Analisis bivariate obtained the results of people who get the intervention has a category less in the effort of prevention of outbreaks of DHF, whereas people who get the intervention have sufficient category in the effort of prevention of outbreaks DHF. Analysis Bivariate using Mann-Whitney test because the data group two paired test pairs are not normally distributed. The result of the research with significant value (p) = 0.000 which means p 0,05 with error rate 5% then H0 is rejected which means health education DHF increase effort of prevention of extraordinary event.